136 Beyond the Aorta: Experiences of Neurovascular Imaging in Loeys-dietz and Vascular Ehlers Danlos Syndrome. (3rd June 2016) - Smith, Carolyn; Mehta, Sarju; Burrows, Nigel; Martin, Peter; Rusk, Rosemary
Abstract : Introduction: The vascular complications of inherited syndromes Loeys-Dietz (LDS) and Vascular Ehlers Danlos (vEDS) lead to significant morbidity and mortality. Current recommendations advocate head to pelvis screening for LDS, and to a lesser extent for vEDS as complications typically involve medium to large arteries. We reviewed the practice in our aortopathy Inherited Cardiac Conditions Clinic (AICC). In our institution these patients are managed by a multi-specialist approach including cardiologists, neurologists, vascular surgeons, chest physicians, dermatologists and geneticists. Methods: Patients were identified through current attendance at AICC or discussion at the linked multidisciplinary team (MDT) meeting. Electronic notes and imaging were reviewed to determine clinical details, genetic diagnosis, screening offered and (neuro) vascular complications. Results: 36 patients were identified. Of these: 14 had a genetic diagnosis of vEDS, 8 a genetic diagnosis of LDS, 4 were excluded (alternate genetic diagnosis e.g. Marfan's) and the remaining 10 had a suggestive clinical phenotype without a typical LDS/vEDS gene mutation and were reviewed alongside the LDS/vEDS population. Screening was performed with separate CT angiograms (arch to carotids and arch to iliacs) to obtain adequate image quality. Two patients had clinical neurovascular events (spontaneous dissection). To date neurovascular imaging has been offered to 27 of the 32 patients (82%). Of these, two patients declined screening, leading to 78% of the patient group being studied (25 of 32). Neurovascular involvement of all patients screened reached 52% (4 vEDS, 4 LDS, 5 other) including a high proportion of the patients (5 of 6 screened) without genetic LDS/vEDS diagnosis (Tables 1, 2; Figure 1 ). Significant neurovascular pathology was identified in the absence of aortic pathology, including one LDS patient with normal aortic dimensions and morphology, a finding not commonly reported in the literature. Conclusions: This is a small population of patients, but the neurovascular involvement rate is high. We would recommend that head to pelvis screening is considered for all LDS and vEDS patients, including those with normal aortic dimensions and morphology. Furthermore, this data implies that patients with a suggestive clinical phenotype should be offered the same screening protocols. It also emphasises the importance of a multi-specialist approach to these patients and their management should not be confined to cardiology alone. Once identified, the specialist MDT is key in making decisions on further surveillance and treatment threshold.